Štrekljev sindrom - Terseglav, Marko (Traditiones (Ljubljana), 2001)
In his work as Editor of the Slovenske narodne pesmi (Slovene Folk Song) anthology (1895-1923) Karel Šrekelj encountered the problem of songs with a known author. Feeling that they were not truly folk songs and that they opposed the rules of dolklore and folk poetics, he most often excluded them from the anthology. Yet the nature of his material forced him to reconsidered his decision. He therefore decided upon a compromise, publishing a supplement of these "non-folk" songs in the 3rd and the 4th volumes of the anthology. Štrekelj's dilemma provoked the author of the papers to wonder how contemporary folkloristics solves problems of this nature. After having examined several field notebooks of the Institute of Ethnomusicology at the Scientific Research Centre of the Slovenian Academy of Arts and Sciences he has discovered that some of Štrekelj's mistakes have been repeated, and that the "folk" aspect of (particulary) more recent and popular songs had beed merely a matter of subjective desicions. The author maintains that such subjective judgements occur because folk poetics ia a living, changing organism; it is therefor not easy to ascertain which songs are folk songs and which are not. Songs "in transition" cannot therefore be automatically rejected as non-folk songs
Keywords: Štrekelj, Karel, 1895-1923; ethnology; etnologija; ljudsko slovstvo; oral literature; slovensko ljudsko slovstvo; ljudske pesmi; Ethnopoetics